Variations in Fungal Community and Diversity in Doushen With Different Flavors - Luo, Qiaoqiao; Zhu, Yan; Zhang, Zhongming; Cao, Yingying; Zhang, Weibing (Frontiers in Microbiology, 2020)
Doushen, a traditional Chinese fermented soybean product, may be spiced or spicy depending on whether pepper powder is added. While numerous studies have investigated the microbial communities of other fermented foods, little is known on the fungal diversity of Doushen. Therefore, in this study, we investigated the fungal community and diversity in both spiced and spicy Doushen. Our results revealed that fungal species richness significantly differed between the samples with different flavors. A total of nine phyla and 188 fungal genera were identified, and Ascomycota and Aspergillus were predominant in all samples. Based on linear discriminant analysis, a total of 57 OTUs were significantly different between the two samples. Results of nonmetric multidimensional scaling and unweighted pair-group analysis suggested that the presence of pepper powder affects the microbial community in Doushen. Network analysis showed that microbial interactions between fungal communities in Doushen with different flavors were significantly different. The results on the enumeration and identification of fungi were consistent with the composition of the dominant genera in the samples with different flavors. This study provides a theoretical basis for future research on food ecology in Doushen.